2020
DOI: 10.1017/bec.2020.9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Australian Psychologists’ Education, Beliefs, Theoretical Understanding, and Attachment on the Use and Implementation of Exposure Therapy

Abstract: The objective of this study was to investigate the relative contributions of university education, exposure specific training, and beliefs about exposure therapy (ET) in relation to the frequency, duration, and intense delivery of ET by Australian psychologists. Associations between clinicians’ use of and theoretical conceptualisation of ET, and attachment style were also evaluated. A total of 115 Australian psychologists (N = 94 females) completed an online survey. Findings revealed that a majority of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(115 reference statements)
1
3
0
Order By: Relevance
“…Findings are consistent with those found across other countries, particularly where samples of psychologists have been used and where training programs have a heavy emphasis on CBT (Sars & van Minnen, 2015). Previous research has highlighted the importance of confidence (Trivasse et al, 2020), beliefs about exposure therapy (Deacon et al, 2013;Schumacher et al, 2018) and knowledge of theoretical underpinnings (Rowe & Kangas, 2020), as has been found here. This research, therefore, provides further support for previously identified barriers to use and for elements that, if addressed in clinical training, may increase use.…”
Section: Changes That Would Increase the Use Of Exposure Therapysupporting
confidence: 90%
See 2 more Smart Citations
“…Findings are consistent with those found across other countries, particularly where samples of psychologists have been used and where training programs have a heavy emphasis on CBT (Sars & van Minnen, 2015). Previous research has highlighted the importance of confidence (Trivasse et al, 2020), beliefs about exposure therapy (Deacon et al, 2013;Schumacher et al, 2018) and knowledge of theoretical underpinnings (Rowe & Kangas, 2020), as has been found here. This research, therefore, provides further support for previously identified barriers to use and for elements that, if addressed in clinical training, may increase use.…”
Section: Changes That Would Increase the Use Of Exposure Therapysupporting
confidence: 90%
“…Whilst meta‐analytic findings have demonstrated that training leads to improvements in knowledge, training has not been reliably demonstrated to increase intention or use of exposure therapy (Trivasse et al, 2020). Whilst CBT is frequently taught in tertiary education and practiced in clinical settings in Australia (Rowe & Kangas, 2020), training programs may not routinely address a clinician's intention or motivation to use exposure therapy, which has been suggested as key to improving the science‐practice gap (Trivasse et al, 2020). Therefore, whilst conventional training may help, the addition of particular components may be required to improve the science‐practice gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Adults (unspecified). (Rowe & Kangas, 2020 ) Quantitative descriptive Survey Anxiety-related presentations (combined anxiety disorders and OCD). Adults (unspecified).…”
Section: Resultsmentioning
confidence: 99%